Posterior reversible encephalopathy syndrome during severe acute pancreatitis - Sato, Masanori; Ifuku, Tassei; Iwashita, Yuji; Nakayama, Hirofumi; Yoshihara, Hideaki; Tokimura, Hiroshi; Hanaya, Ryosuke (Nepal Journal of Neuroscience, 2025)
Posterior reversible encephalopathy syndrome (PRES) is a relatively rare central nerve condition. Here, we report a case of PRES that developed during acute pancreatitis in a previously healthy man in his 40s. On the third day, his respiratory status worsened during management of acute pancreatitis, requiring sedated ventilatory support. During ventilator management, his blood pressure was well-controlled, and no electrolyte abnormalities were observed; however, the patient was in a state of marked systemic inflammation. On the 12th day, after improvement in acute pancreatitis and respiratory status, with discontinuation of mechanical ventilation, the patient presented with mild disturbance of consciousness and visual field disturbance. Magnetic resonance imaging (MRI) showed diffuse vasogenic cerebral edema, mainly in the bilateral occipital and parietal white matter. The patient was provisionally diagnosed with PRES and was administered oral verapamil, along with supportive care. On the 23rd day, his neurological symptoms disappeared. Cerebral edema completely disappeared on MRI four months later. In the present case, it was speculated that endothelial dysfunction secondary to the severe inflammatory state accompanying acute pancreatitis caused PRES.